Accuracy assessment of global barotropic ocean tide models. (7th August 2014) - Stammer, D.; Ray, R. D.; Andersen, O. B.; Arbic, B. K.; Bosch, W.; Carrère, L.; Cheng, Y.; Chinn, D. S.; Dushaw, B. D.; Egbert, G. D.; Erofeeva, S. Y.; Fok, H. S.; et al.
Abstract The accuracy of state‐of‐the‐art global barotropic tide models is assessed using bottom pressure data, coastal tide gauges, satellite altimetry, various geodetic data on Antarctic ice shelves, and independent tracked satellite orbit perturbations. Tide models under review include empirical, purely hydrodynamic ("forward"), and assimilative dynamical, i.e., constrained by observations. Ten dominant tidal constituents in the diurnal, semidiurnal, and quarter‐diurnal bands are considered. Since the last major model comparison project in 1997, models have improved markedly, especially in shallow‐water regions and also in the deep ocean. The root‐sum‐square differences between tide observations and the best models for eight major constituents are approximately 0.9, 5.0, and 6.5 cm for pelagic, shelf, and coastal conditions, respectively. Large intermodel discrepancies occur in high latitudes, but testing in those regions is impeded by the paucity of high‐quality in situ tide records. Long‐wavelength components of models tested by analyzing satellite laser ranging measurements suggest that several models are comparably accurate for use in precise orbit determination, but analyses of GRACE intersatellite ranging data show that all models are still imperfect on basin and subbasin scales, especially near Antarctica. For the M2 constituent, errors in purely hydrodynamic models are now almost comparable to the 1980‐era Schwiderski empirical solution, indicating marked advancement in dynamical modeling. Assessing model accuracy using tidal currents remains problematic owing to uncertainties in in situ current meter estimates and the inability to isolate the barotropic mode. Velocity tests against both acoustic tomography and current meters do confirm that assimilative models perform better than purely hydrodynamic models.